Lipids infused into the jejunum accelerate small intestinal transit but delay ileocolonic transit of solids and liquids. Issue 1 (1st July 1998) - Hammer, J; Hammer, K; Kletter, K
Abstract : Background —Various nutrients are known to alter small intestinal motility patterns although their effect on transit of fluids and solids in man is not clear. Aims —To determine small intestinal transit of solids and liquids during perfusion with lipids, protein, and non-energy solutions. Methods —Twenty eight healthy volunteers received a jejunal infusion (1 ml/ minute for 30 minutes) of one of four solutions: a lipid or a protein solution (4.18 J/ml), a non-absorbable electrolyte solution containing polyethylene glycol, or 0.9% sodium chloride. As solid phase marker 1 g of amberlite resin pellets labelled with 111 InCl3 was added; 99m Tc DTPA was used as a fluid phase marker. Images were obtained on a gamma camera at 10 minute intervals for four hours or until all radiolabel was detected in the colon. Results —Intestinal transit of solids and liquids from the duodenojejunal junction to the caecum was simultaneous, and independent of the energy content of the solution infused. Lipid infusion accelerated transit through the small intestine but delayed transport of chyme along the ileocolonic junction. After protein small intestinal transit was slowest; ileocolonic transit on the other hand was fastest with protein. Transit of the non-energy solutions was in between that of the nutrient solutions. Conclusions —Transit times through the small intestine and the ileocolonic junction were influenced by the luminal contents. In the small intestine fat induced significantly faster transit compared with proteins, but delayed ileocolonic transit. Once in the small intestine, solids and liquids transit the small bowel together, independent of the luminal content.